Physical condition, global self-esteem and academic performance in adolescence (International Seven Journal of Multidisciplinary, 2024)
To better understand the global self-esteem of adolescents, to know how global self-esteem and different levels of physical fitness are related; to know how global self-esteem is related to male versus female gender. And determining how global self-esteem is associated with academic performance, according to gender and age, is an important and pertinent task in the current school context.The sample of this study consists of 1,327 participants, 711 females (53.58%), aged between 12 and 17. Physical condition was assessed using the Fitnessgram; academic performance using the arithmetic average of subjects and global self-esteem using the Rosenberg global self-esteem scale (1965), adapted by Romano, Negreiros and Martins (2007). It was found that there was no statistically significant relationship between the different physical condition groups and global self-esteem, in the overall sample and in both sexes. In the overall sample, global self-esteem is not significantly associated with academic performance. In males, the correlation is significant, positive and weak. In females, the correlation is not significant. Overall self-esteem is not related to age, in the total sample and in both sexes.The self-esteem of male participants differs statistically significantly from that of females.